Pelatihan Tajwid untuk Pengajar dan Santri TPQ di Desa Dukuharum Di TPQ Al Hidayah - sutrisno, sutrisno; `Mas’ud, Mas’ud (ABDIMASY: Jurnal Pengabdian Kepada Masyarakat, 2024)
. Current developments have both positive and negative roles in the fields of science and religion, for example in every TPQ where the majority of children underestimate the issue of reading the Qur'an, and few want to learn the science of recitation. The majority of Muslims have learned to read the Al-Qur'an, either through elementary schools (SD) or Al-Qur'an Educational Parks (TPQ), but not everyone is able to read the Al-Qur'an well and correctly, because the condition is that someone can can be said to be smart and proficient in reading the Qur'an, namely by mastering the science of tajwid, including makhorijul letters (where the letters come out), alatul letters (the properties of each letter), akhamul letters (laws of letters), mad wal qashar (length and short letters), waqof wal inida' (a place to stop and start reading again). Society, especially children, are future assets that really need to be nurtured in the form of Islamic character. This community service is realized in the form of training in learning the science of recitation for teachers (ustad/ustadzah) and children at TPQ Al Hidayah, Dukuharum Village.